Val66Met BDNF Gene Polymorphism Influences Human Motor Cortex Plasticity in Acute Stroke. - Di Lazzaro, V; Pellegrino, G; Di Pino, G; Corbetto, M; Ranieri, F; Brunelli, N; Paolucci, M; Bucossi, S; Ventriglia, M; Brown, P; Capone, F (Elsevier, 2015)
BACKGROUND: BDNF gene polymorphism impacts human motor cortex function and plasticity. OBJECTIVE/HYPOTHESIS: Using transcranial magnetic stimulation (TMS), we investigated whether BDNF polymorphism influences cortical plastic changes in acute stroke. METHODS: Twenty patients were recruited within 10 days of their first-ever ischemic stroke and genotyped for BDNF polymorphism. Blinded to the latter, we evaluated the excitability of the affected and unaffected hemisphere by measuring resting and active motor threshold and motor-evoked potential amplitude under baseline conditions and after intermittent theta burst stimulation, a protocol of repetitive TMS inducing LTP-like activity. We also computed laterality indexes to assess inter-hemispheric excitability imbalance. RESULTS: Demographics, threshold and amplitude of motor-evoked potentials did not differ between those with (8 patients) and without polymorphism. Excitability of the unaffected hemisphere was significantly higher than the excitability of the affected hemisphere as probed by each measure. This imbalance was exaggerated in those without polymorphism; laterality indexes of rest motor thresholds were 0.016 ± 0.050 and 0.139 ± 0.028 for patients with and without polymorphism [t = 2.270, P = 0.036]. Exaggerated hemispheric imbalance also persisted after intermittent theta burst stimulation, which failed to induce any difference between groups. CONCLUSIONS: Our results suggest that inter-hemispheric imbalance with greater excitability over unaffected hemisphere, is several times stronger in stroke patients without, as opposed to with, polymorphism.